PCR technique for detection of Giardia lamblia in microscopically positive stool samples of the patients in Al-Diwaniyah hospital /Iraq. - Al- haidare, Dhamiaa Maki Hamza; Ali Mala, Saba Fadhil (Al-Qadisiyah Journal of Pure Science, 2018)
Giardia lamblia is one of the most common human parasites and causes a lengthily course of nonbacterial diarrhea. Disease outbreaks due to Giardia infection are often attributed to contaminated food and water supplies. A major problem associated with detection for this organism is the lack of sensitive and reliable methods. PCR has the potential to address many of the limitations. We have performed a PCR-based method for sensitive detection of Giardia. Because the sensitivity of PCR is a function of the efficiency of DNA extraction from parasite. Giardia samples were collected from stool of infected persons and first detected microscopically and the second step used of the PCR technique to ensure the infection,DNA was extracted and used of a 619 bp conserved fragment related to the DNA was extracted ,and the GL50803_17190 Eukaryotic peptide chain release factor subunit 1[Giardia lamblia ATCC 50803 ]gene was used as the target for PCR amplification which rarely used. The results suggest the potential utilities of PCR for sensitive detection of G.Lamblia which isolated from stool of infected persons with Giardiasis.